1996
DOI: 10.1136/jnnp.61.1.47
|View full text |Cite
|
Sign up to set email alerts
|

The A to G transition at nt 3243 of the mitochondrial tRNALeu(UUR) may cause an MERRF syndrome.

Abstract: Objective-To verify the phenotype to genotype correlations of mitochondrial DNA (mtDNA) related disorders in an atypical maternally inherited encephalomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…2,3,6,7 Atrophy of the brain stem and superior cerebellar peduncles and signal intensity abnormalities of the brain stem were not described. The present study describes these abnormalities in patients with MERRF, and the results are supported by previous neuropathologic studies that showed degeneration of the brain stem and dentate nuclei as well as the basal ganglia, cerebellar cortices, and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,6,7 Atrophy of the brain stem and superior cerebellar peduncles and signal intensity abnormalities of the brain stem were not described. The present study describes these abnormalities in patients with MERRF, and the results are supported by previous neuropathologic studies that showed degeneration of the brain stem and dentate nuclei as well as the basal ganglia, cerebellar cortices, and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…The A8344G or A3243G mutations of mitochondrial deoxyribonucleic acid (DNA) are the genetic causative factors. [1][2][3] The clinical phenotype and prognosis are better for patients with the A8344G mutation than for those with the A3243G mutation. 3 Mitochondrial DNA mutation is heteroplasmic, and normal DNA and mutant DNA coexist within the same individual.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, patients can have the genetic mutation but be phenotypically normal 13,27,41 or display characteristics of other mtDNA syndromes. 31,[42][43][44] As well, genetic testing is relatively insensitive: patients can have symptomatic mtDNA disorders with negative screen results for common mtDNA mutations. 37,41,45 Presumably these latter patients have either genetic defects not yet described [46][47][48] or genetic defects focused in tissues not used to prepare the mtDNA for the assay.…”
Section: Commentmentioning
confidence: 99%
“…63 The most common mutation observed in MELAS, the A3243G in tRNA Leu(UUR) has also been described in MERRF patients, with no MELAS symptoms. 64,65 Similarly to MELAS, many overlap syndromes have been associated with mt-tRNA mutations like MERRF/MELAS and MELAS/MERRF/Kearns-Sayre. Peculiarly, a MERRF/PEO overlap syndrome associated with the A3243G mutation in tRNA Leu(UUR) has also been described, 66 and a MERRF/Kearns-Sayre syndrome has been associated with the G3255A mutation in tRNA Leu(UUR) .…”
Section: The Clinical Phenotypes Of Mitochondrial Trna Mutationsmentioning
confidence: 99%